Nehru : the invention of India - Tharoor, Shashi (Arcade Pub. : Distributed by AOL Time Warner Book Group, 2003)
"Born into a wealthy, politically influential Indian family in the waning years of the Raj, Jawaharlal Nehru was raised, under his father's careful guidance, on Western secularism and the humanist ideas of the Enlightenment. But it was not until he met Gandhi in 1916 that Nehru was transformed from an uninspired student into a fiery and motivated activist. The theories of democracy, human dignity, and self-determination from his student days became ideals to fight and live for. In Nehru and Gandhi, India found an invincible team - a spiritual father who could move millions and a political tactician who could galvanize them into action. Together, they led the nonviolent struggle for India's independence, a struggle that wasn't won until 1947. But neither Nehru nor Gandhi could prevent the horrific price for independence: partition." "In this fascinating account of an extraordinary life and career, Shashi Tharoor, eminent United Nations diplomat and author of India: From Midnight to the Millennium, traces Nehru's development from privileged child, posturing young nationalist, and valiant fighter for independence, to unchallengeable prime minister and global statesman. Tharoor casts an unflinching eye on Nehru's heroic efforts for, and stewardship of, independent, India and gives us a careful appraisal of his legacy to the world."--BOOK JACKET.